Medical education in Israel 2016: five medical schools in a period of transition. Issue 1 (December 2016) - Reis, Shmuel; Urkin, Jacob; Nave, Rachel; Ber, Rosalie; Ziv, Amitai; Karnieli-Miller, Orit; Meitar, Dafna; Gilbey, Peter; Mevorach, Dror
Abstract We reviewed the existing programs for basic medical education (BME) in Israel as well as their output, since they are in a phase of reassessment and transition. The transition has been informed, in part, by evaluation in 2014 by an International Review Committee (IRC). The review is followed by an analysis of its implications as well as the emergent roadmap for the future. The review documents a trend of modernizing, humanizing, and professionalizing Israeli medical education in general, and BME in particular, independently in each of the medical schools. Suggested improvements include an increased emphasis on interactive learner-centered rather than frontal teaching formats, clinical simulation, interprofessional training, and establishment of a national medical training forum for faculty development. In addition, collaboration should be enhanced between medical educators and health care providers, and among the medical schools themselves. The five schools admitted about 730 Israeli students in 2015, doubling admissions from 2000. In 2014, the number of new licenses, including those awarded to Israeli international medical graduates (IMGs), surpassed for the first time in more than a decade the estimated need for 1100 new physicians annually. About 60 % of the licenses awarded in 2015 were to IMGs. Conclusions Israeli BME is undergoing continuous positive changes, was supplied with a roadmap for even further improvement by the IRC, and has doubled its output of graduates. The numbers of both Israeli graduates and IMGs are higher than estimated previously and may address the historically projected physician shortage. However, it is not clear whether the majority of newly licensed physicians, who were trained abroad, have benefited from similar recent improvements in medical education similar to those benefiting graduates of the Israeli medical schools, nor is it certain that they will benefit from the further improvements that have recently been recommended for the Israeli medical schools. Inspired by the IRC report, this overview of programs and the updated physician manpower data, we hope the synergy between all stakeholders is enhanced to address the combined medical education quality enhancement and output challenge.